Oxford international english: teacher resource book 2 - Snashall, Sarah (Oxford University Press Karachi, 2017)
This Teacher Resource Book provides step-by-step guidance on delivering effective lessons and assessing pupils' progress to ensure core skills are taught in a consistent way.